Pengendalian Dorongan Seksual melalui Peningkatan Peran Orang Tua dan Aktivitas Santriwati - Samara Rahma Dania; Lutfi Agus Salim (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2019)
One of adolescence’s problems is uncontrolable sexual drive. It was expected that the students of Islamic boarding school have a sexual driving better than students of common school. But, sexuality problem among boarding school’s student is similar with student in common school. Good sexual driving can protect the students from negative impacts of sexual activity. Sexual driving is influenced by parent’s role and student activity. This study aimed to analyse the relationship between parent’s role and student activity with sexual driving of female student in islamic boarding school in Sukoharjo City. The research was taken on April, 2019. The subjects were 107 students in the age of 10–18 who study at Madrasah Aliyah (MA) Pondok Pesantren X andY, Kabupaten Sukoharjo. Research method is cross-sectional. Sampling technique was stratified random sampling, whereas data collection technique is interview using questionnaire. The data were a analyzed with chi-square (p value < 0,005). The result showed that parent’s role has significant relationship with sexual driving (p value < 0,005), whereas activity do not have relationship with sexual driving (p value > 0,05). Parent’s role was giving direction to their children to have good behavior. Student who has good faith will avoid something that prohibited in Islam. Although student of Islamic Boarding School has leisure time, regulation of Islamic boarding school makes them are avoided from negative sexual activity.